SERBIA AND MONTENEGRO: THE NEW LEGAL FRAMEWORK FOR THE PROTECTION OF ETHNIC MINORITIES - Krivokapić, Boris (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2003)
In the beginning of 2003, the Federal Republic of Yugoslavia was reconstituted as the State Union of Serbia and Montenegro. The reconstitution was legalized by the Constitutional Charter of Serbia and Montenegro of March 27th, 2003. The fate of this union is pretty uncertain as it remains to be seen whether it will survive and in which form, or whether the associated republics, Serbia on the one side, and Montenegro on the other, shall soon separate. However, life goes on. In the last few years, even months, certain changes of the legal system were introduced in Yugoslavia. Among these changes, particularly interesting were those related to the regulation of rights and the situation of ethnic minorities. The analysis of the legal regulations of a certain state logically starts with its supreme legal act, its constitution, and then continues to its other relevant statutes and regulations. Still, having in mind the current realities of Serbia and Montenegro, a form of chronological order seems more suitable. Therefore, after the introductory notes, the Federal Act on Protection of Rights and Freedoms of National Minorities (adopted in 2002 in the Federal Republic of Yugoslavia and still in effect) will be presented, with the relevant supreme legal acts of the State Union of Serbia and Montenegro after that.